PHAST. The Panchromatic Hubble Andromeda Southern Treasury. I. Ultraviolet and Optical Photometry of over 90 Million Stars in M31 - Zhuo Chen; Benjamin Williams; Dustin Lang; Andrew Dolphin; Meredith Durbin; Julianne J. Dalcanton; Adam Smercina; Léo Girardi; Claire E. Murray; Eric F. Bell; Martha L. Boyer; Richard D’Souza; et al. (The Astrophysical Journal)
The Panchromatic Hubble Andromeda Southern Treasury (PHAST) is a large 195-orbit Hubble Space Telescope program imaging ∼0.45 deg ^2 of the southern half of M31's star-forming disk at optical and near-ultraviolet (NUV) wavelengths. The PHAST survey area extends the northern coverage of the Panchromatic Hubble Andromeda Treasury (PHAT) down to the southern half of M31, covering out to a radius of ∼13 kpc along the southern major axis and in total ∼two-thirds of M31's star-forming disk. This new legacy imaging yields stellar photometry of over 90 million resolved stars using the Advanced Camera for Surveys in the optical (F475W and F814W), and the Wide Field Camera 3 (WFC3) in the NUV (F275W and F336W). The photometry is derived using all overlapping exposures across all bands, and achieves a 50% completeness-limited depth of F475W ∼ 27.7 in the lowest surface density regions of the outer disk and F475W ∼ 26.0 in the most crowded, high surface brightness regions near M31's bulge. We provide extensive analysis of the data quality, including artificial star tests to quantify completeness, photometric uncertainties, and flux biases, all of which vary due to the background source density and the number of overlapping exposures. We also present seamless population maps of the entire M31 disk, which show relatively well-mixed distributions for stellar populations older than 1–2 Gyr, and highly structured distributions for younger populations. The combined PHAST + PHAT photometry catalog of ∼0.2 billion stars is the largest ever produced for equidistant sources and is available for public download by the community.